Silica Nanoparticles Promote α-Synuclein Aggregation and Parkinson’s Disease Pathology - Yuan, Xin; Yang, Yingxu; Xia, Danhao; Meng, Lanxia; He, Mingyang; Liu, Chaoyang; Zhang, Zhentao (Frontiers in Neuroscience, 2022)
Silica nanoparticles (SiO2 NPs) are increasingly investigated for their potential in drug delivery systems. However, the neurotoxicity of SiO2 NPs remains to be fully clarified. Previously SiO2 NPs have been reported to be detected in the central nervous system, especially in the dopaminergic neurons which are deeply involved in Parkinson’s disease (PD). In this article, we characterized the effects of SiO2 NPs on inducing PD-like pathology both in vitro and in vivo. Results showed that SiO2 NPs promote more severe hyperphosphorylation and aggregation of α-synuclein, mitochondria impairment, oxidative stress, autophagy dysfunction, and neuronal apoptosis in the α-Syn A53T transgenic mice intranasally administrated with SiO2 NPs compared with the control group. Our findings provide new evidence supporting that SiO2 NPs exposure might have a strong capability of promoting the initiation and development of PD.